Neonatology simple and easy. Part 3 - Brucknerová, Ingrid (Univerzita Komenského v Bratislave, 2016)
The third part of "Neonatology, Simple and Easy", which will deal with further very characteristic problems of the newborn. Examination of the respiratory system, especially in the neonatal period, is the dominant topic of the book, along with a focus on changes that occur physiologically after birth. This book is intended to give students of medicine a comprehensive view by presenting differential diagnosis of different causes of respiratory insufficiency with accentuation on respiratory and cardiac causes from the first moments of age and during the neonatal period. A further aim is to alert readers to the use of logical steps, which are based on knowledge about the development of the respiratory system, etiology, pathophysiology and specifics of respiratory insufficiency. Only logical thinking, prudent judgment/opinion and thought out procedure will help students to master the most difficult problems of the neonate.